Al-Jihād al-insānī: Shumūlīyat "al-Muhammadīyah" fi muḥārabat ja'ihat COVID-19 - Bakhtiar Bakhtiar; Salma Salma (Studia Islamika, 2022)
The Covid-19 pandemic has jolted the world, including Indonesia. The transmission is extremely quick, huge, and difficult to identify. Millions of people have been infected, and some have died as a result. Vaccines and medicines that are effective have yet to be discovered. This extraordinary situation deserves exceptional handling from all sides. This research attempts to explain Muhammadiyah’s humanitarian jihad by mobilizing all of its resources using an empirical method and referencing the study of social fiqh-praxis. This study illustrates Muhammadiyah’s humanitarian struggle in sustaining and safeguarding life against the real threat of Covid-19. During the management of Covid-19, their efforts resulted in religious fatwas and humanitarian initiatives by involving all resources. The rise of this humanitarian struggle is the result of a genuine and unprecedented challenge to the soul and integrity of Muhammadiyah. This kind of jihad has ramifications for worship practices, activities, and organizational actions that include the public.